BIOLOGY OF PSETTODES ERUMEI (SCHNEIDER, 1801) AND PSEUDORHOMBUS ARSIUS (HAMILTON, 1822) FROM THE NORTHERN ARABIAN SEA - Hussain, Syed Makhdoom (Indian Journal of Fisheries, 2011)
The flatfishes (Pleuronectiformes) are represented by four families and 28 spedes along Sind and Makrancoasts (northern Arabian Sea). Psetlodes erumei and Pseudorhombus arsius contribute major portion ofthe flatfishes caught from these coasts. The two spedes are distributed in coastal waters, shelf area andoff shore waters. P. arsius migrates into aedcs and estuaries. The analysis of length and weight relationshipshowed isometric growth in both spedes. Studies on food contents revealed higher percentage ofinvertebrate in juvenile fishes and as fishes grow they change over to fish as major food. Dial differencein feeding habit is also noted in two spedes. Spawning seems to occur from March to May, before onsetof monsoon in P. erumei and after monsoon, September - November in P. arsius